MODIFIKASI PARALLEL ENCRYPTION WITH DIGIT ARITHMETIC AND COVERTEXT (PDAC) MENGGUNAKAN KUNCI BERULANG - Eka Ardhianto (Jurnal Informatika Universitas Pamulang, 2022)
The encryption process is the most important security technique, because it is used to hide information from unauthorized parties. With the ability to secure large amounts of data, encryption is of utmost importance. The aim of this research is to be able to hide a large amount of information by using a repetitive key to the solution for an odd number of plaintext characters for smooth encryption in PDAC. In this study, the mathematical operations of addition and subtraction are used to generate keys from ASCII codes. The result of this research is an increase in the capacity of information that can be secured